The Values of Monotheism Internalized to the Younger Generation in Islamic Religious Education Subjects with Surah Al-Fatihah - Taufiq, Gusman (Journal Sains and Education, 2023)
This study aims to examine more deeply the values of monotheism that are internalized in the younger generation in Islamic religious education subjects and their implementation in everyday life. This study uses a qualitative approach which intends to understand what phenomena are experienced by research subjects. The results of the study show that the concept of internalizing the values of monotheism is a process of instilling something, beliefs, attitudes and values that become social behavior. However, the planting process grows from within a person to the appreciation of a value. While the value itself is the essence of a thing that causes it to be pursued by humans. Implementation of the Concept of Monotheism Values In Senior high school students, activities in schools such as routine activities, spontaneous activities, exemplary and conditioning are a way of instilling divine values education to students in the school environment. , Verse 1 contains the character value of getting used to saying the name of Allah in every activity, Verse 2 contains the character value of gratitude. Verse 3 contains the character value of politeness, Verse 4 contains the character value of working hard, Verse 5 contains the character value of humility, Verse 6 contains the character value of being aware of rights and a sense of mutual help and Verse 7 contains the character value of always trying to do good .